Integrated chemicals policy: seeking new direction in chemicals management (Lowell, MA, 2003)
"This briefing paper presents a publicly accessible overview of the problems of current chemicals management efforts and the need for a new approach. It summarizes efforts moving forward in Europe, the United States and internationally on integrated chemicals policy."